THE LEGAL CAPACITY IN CONTRACT FOR MEDICAL TREATMENT (THE COMPARATIVE STUDY BETWEEN INDONESIAN LAW, DUTCH LAW, AND ENGLISH LAW) - Sri Ratna Suminar; Yoni Fuadah Syukriani; U Sudjana; Efa Laela Fakhriah (Jurnal Bina Mulia Hukum, 2020)
This article aims to determine the criterion of legal capacity of a patient in a contract for medical treatment and the legal consequences of a contract for medical treatment made by a minor. This article uses a normative juridical research method with a law approach and the data sources used are obtained from literature studies and document studies, and study results showed that there is a similar criterion for determining whether a patient is competent or not in giving consent for medical treatment between Indonesian law and Dutch law that is based on a legally fixed age. However, based on Dutch law, the age of legal capacity to consent for medical treatment differs from the age of legal majority. Meanwhile, English law uses mixed approaches to determine a minor capacity in giving consent for medical treatment that is based on the age and competence of a minor. Furthermore, according to Indonesian Law, a contract for medical treatment made by minors is voidable, whereas according to Dutch Law and also English Law any contract for medical treatment made by minors is legally binding.